Supervised versus autonomous exercise training in breast cancer patients: A multicenter randomized clinical trial. (10th November 2018) - Westphal, Theresa; Rinnerthaler, Gabriel; Gampenrieder, Simon Peter; Niebauer, Josef; Thaler, Josef; Pfob, Michael; Fuchs, David; Riedmann, Marina; Mayr, Barbara; Reich, Bernhard; Melchardt, Thomas; Mlineritsch, Brigitte; et al.
Abstract: Background: There is a well‐known correlation between obesity, sedentary lifestyle, and breast cancer incidence and outcome. The Arbeitsgemeinschaft Medikamentöse Tumortherapie (AGMT) exercise study was a multicenter, randomized clinical trial and assessed the feasibility and efficacy of physical training in 50 breast cancer patients undergoing aromatase inhibitor treatment. Methods: Postmenopausal, estrogen receptor‐positive breast cancer patients under aromatase inhibitor treatment were randomized 1:1 to counseling and unsupervised training for 48 weeks (unsupervised arm) or counseling and a sequential training (supervised arm) with a supervised phase (24 weeks) followed by unsupervised physical training (further 24 weeks). Primary endpoint was the individual maximum power output on a cycle ergometer after 24 weeks of exercise. A key secondary endpoint was the feasibility of achieving 12 METh/week (metabolic equivalent of task hours per week). Results: Twenty‐three patients (92%) in the unsupervised arm and 19 patients (76%) in the supervised arm with early‐stage breast cancer completed the study. After 24 weeks, the supervised arm achieved a significantly higher maximum output in watt (mean 132 ±  standard deviation [SD] 34; 95% confidence interval [CI] 117‐147) compared to baseline (107 ± 25; 95%CI 97‐117; P  = 0.012) with a numerically higher output than the unsupervised arm (week 24 115 ± 25; 95%CI 105‐125; P  = 0.059). Significantly higher METh/week was reported in the supervised arm compared to the unsupervised arm during the whole study period (week 1‐24 unsupervised: 18.3 (7.6‐58.3); supervised: 28.5 (6.7‐40.1); P  = 0.043; week 25‐48; P  = 0.041)). Conclusion: This trial indicates that patients in an exercise program achieve higher fitness levels during supervised than unsupervised training. Abstract : Our findings on breast cancer patients under aromatase inhibitor treatment indicate that patients achieve higher fitness levels during supervised training compared to unsupervised training.